2018
DOI: 10.1111/sjop.12490
|View full text |Cite
|
Sign up to set email alerts
|

Who are the high achievers at work? Perceived motivational climate, goal orientation profiles, and work performance

Abstract: The purpose of this study was to respond to the call for research on goal orientation (mastery and performance orientation) profiles in work contexts. Among 8,282 engineers and technologists, Latent profile analyses indicated that four different goal orientation profiles existed – primarily mastery oriented, indifferent, moderate multiple goals, and success oriented. Both success oriented employees and employees who are primarily mastery oriented indicated the highest individual work performance. Further, mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 101 publications
(263 reference statements)
0
13
0
Order By: Relevance
“…Motivation in the practice of physical activity is a concept that has been studied worldwide as it is a fundamental issue nowadays [39,40,41,42,43]. After analyzing the results obtained, an inverse relationship between the task and the ego climate is observed in Spanish students, showing that an increased involvement in the task climate is associated with a decreased involvement in the ego-oriented climate.…”
Section: Discussionmentioning
confidence: 99%
“…Motivation in the practice of physical activity is a concept that has been studied worldwide as it is a fundamental issue nowadays [39,40,41,42,43]. After analyzing the results obtained, an inverse relationship between the task and the ego climate is observed in Spanish students, showing that an increased involvement in the task climate is associated with a decreased involvement in the ego-oriented climate.…”
Section: Discussionmentioning
confidence: 99%
“…From the classical theory perspective, this finding implies the acceptance of the 2 × 2 model as a basic goal orientation model (Elliot and McGregor, 2001;Harackiewicz and Linnenbrink, 2005). Simultaneously, this measure can be crucial for future undergraduate students' employability in terms of work performance (Nerstad et al, 2018). However, from the IRT perspective, a deeper analysis of the items is necessary to improve measurement precision of the instrument with respect Ecuadorian students' range of goal orientations.…”
Section: Discussionmentioning
confidence: 99%
“…[24] were looking at the role of goal orientation on work engagement and creativity and found that learning goal orientation strengthened, and performance goal orientation weakened, the links between proactive management and engagement, and between engagement and creativity. Similarly, research on goal orientation (both learning and performance orientation) profiles in work contexts, conducted by Nerstad, Richardsen, and Roberts [25] on a big sample of more than 8200 engineers and technologists, noted that learning and performance climates are relevant antecedents of employees' goal orientation profiles.…”
Section: Literature Review 21 Two Facets Of An Individual's Goal Orie...mentioning
confidence: 94%